Farrow-to-Finish Swine Cost-Return Budget - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S.; DeRouchey, Joel (My University, 2009)
This publication examines the cost and returns for farrow to finish swine production in Kansas.
MF292_2009_12
Keywords: MF292; Livestock; Economics; MF